Mechanism Underlying the Alveolar Bone Destruction by Prevotella intermedia: Systematic Review - Erik Idrus; Sammy Fajar Nugraha; Sri Angky Soekanto (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2023)
Introduction: Periodontitis is an inflammatory disorder caused by oral microorganisms, including Prevotella intermedia, that destroy the periodontal ligament and alveolar bone. The detailed mechanism of P. intermedia-inducing bone damage is essential to establish a novel approach to controlling P. intermedia that prevents alveolar bone loss. Purpose: To elucidate the mechanism of P. intermedia's role in alveolar bone destruction by systematically reviewing various related publications. Methods: From September 2020 through February 2021, this systematic review was performed by selecting publications for relevant material from two electronic databases, PubMed and Scopus. The literature must be in English, published within the last ten years, be available in full-text form, and be a research article to meet the criteria for inclusion. Results: Three final articles passed the eligibility evaluation stage and met the inclusion requirements. They all discussed how P. intermedia lipopolysaccharide (LPS) affects target cells to destroy bone, including human dental follicle stem cells (hDFSCs), human periodontal ligament fibroblasts (hPDLs), and macrophages. Tumor necrosis factor (TNF), interleukin-6 (IL-6), IL-8, and prostaglandin E2 (PGE2) are a few of the inflammatory mediators that LPS P. intermedia cause a rise in target cells, leading to bone damage. These inflammatory mediators stimulate nuclear factor-kappa ligand receptor (RANKL) expression, resulting in osteoclast activation and differentiation, leading to bone loss. Conclusion: P. intermedia significantly contributes to alveolar bone degradation by enhancing inflammatory mediators. As observed in periodontitis, these mediators stimulate RANKL expression and osteoclast activation, resulting in alveolar bone damage.